2001
DOI: 10.1021/es0101532
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoroacetate in Ocean Waters

Abstract: Trifluoroacetate (TFA) is a ubiquitous xenochemical presently increasing in concentration in some environmental compartments, especially in the plant biomass of industrialized countries. Direct anthropogenic emissions of TFA are probably low, and the major anthropogenic sources are most likely various TFA precursors. As TFA has been found in ocean waters from remote locations, the question arose whether it is also a naturally occurring environmental chemical. Determination of the depth dependence of TFA in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
56
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 18 publications
2
56
0
Order By: Relevance
“…TFA has become a ubiquitous contaminant and has been detected in a variety of environmental media, such as air (Frank et al, 1996), precipitation (Jordan and Frank, 1999;Scott et al, 2006;Zehavi and Seiber, 1996), fog (Römpp et al, 2001), surface waters (Cahill and Seiber, 2000;Scott et al, 2000Scott et al, , 2002Zhang et al, 2005), soils and pine needles Scott et al, 2005b), oceans (Frank et al, 2002;Scott et al, 2005a) and even in the snow of the Arctic and Antarctica (Von Sydow et al, 2000). TFA is extremely stable in the ambient and highly resistant to chemical and biological degradation under normal environmental condition (Emptage et al, 1997;Boutonnet et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TFA has become a ubiquitous contaminant and has been detected in a variety of environmental media, such as air (Frank et al, 1996), precipitation (Jordan and Frank, 1999;Scott et al, 2006;Zehavi and Seiber, 1996), fog (Römpp et al, 2001), surface waters (Cahill and Seiber, 2000;Scott et al, 2000Scott et al, , 2002Zhang et al, 2005), soils and pine needles Scott et al, 2005b), oceans (Frank et al, 2002;Scott et al, 2005a) and even in the snow of the Arctic and Antarctica (Von Sydow et al, 2000). TFA is extremely stable in the ambient and highly resistant to chemical and biological degradation under normal environmental condition (Emptage et al, 1997;Boutonnet et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Even so, all these sources mentioned above still could not explain huge reserve of TFA in oceans. During 1998During -1999 when HCFCs/HFCs and fluoropolymers were comparatively less used, TFA levels of about 200 ng L − 1 were homogeneously distributed in ocean waters of the Mid-Atlantic Ocean and the Southern Ocean, even in the depth of below 4,000 m (Frank et al, 2002). Harnisch et al (2000) pointed out that TFA was a naturally occurring chemical with unknown natural sources.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Longer chain (≥C 2 ) PFCAs and all PFSAs are currently thought to arise solely from the use of commercial perfluorinated surfactants, whereas the C 1 PFCA (trifluoroacetic acid; TFA) is both used itself in industry and can also be formed via the oxidative degradation of various precursors such as hydrofluorocarbons, anesthetics, trifluoromethylbenzene based pesticides, and waste incineration. [8][9][10] It has been suggested that continuous low level TFA releases from biological and/or geological sources must be present to account for the mass of this compound (ca. 250 to 300 million tons) in global oceans, whereas terrestrial, freshwater, and atmospheric reservoirs are primarily anthropogenically derived.…”
Section: Introductionmentioning
confidence: 99%
“…250 to 300 million tons) in global oceans, whereas terrestrial, freshwater, and atmospheric reservoirs are primarily anthropogenically derived. [8,11,12] In general, total PFSA and PFCA concentrations in surface and ground waters and marine systems range widely from the low ng L -1 to low mg L -1 levels depending on age and the proximity to point and nonpoint sources of contamination. [3,7, Wastewaters from semiconductor fabrication plants using photolithographic techniques have the highest reported PFA levels to date, with concentrations reaching well into the mg L -1 range, [75] and even up to g L -1 levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation